Performance indicators of energy security and sustainable tourism in enhancing service innovation of island tourism - Siew, Kar Man; Ramachandran, Sridar; Kunasekaran, Puvaneswaran; Mohammad Afandi, Syamsul Herman; Fatin Nornajla; Shuib, Ahmad; Prabhakaran, Sudesh (IDOSI Publications, 2017)
The purpose of this study is to demonstrate the importance on the sustainable tourism initiatives and consideration of energy in the development of better policy towards innovation of tourism. The study is conducted at an internationally well-known tourism island, Mabul Island. Since natural resources on island are scarce and limited, island tourism usually face sustainability issue in terms of energy and tourism development. Moreover, there is lack of sustainability study on energy security specifically on island tourism among local community. Quantitative approach is used for the study where local communities are interviewed using face to face interview technique. Exploratory factor analysis is used to reduce the dimension on both energy security and sustainable tourism variables. Findings from this study revealed eleven components that were grouped and given new title. The contribution of new scale of energy security and sustainable tourism will assist policy makers to review and revise Malaysia’s plans and policies working towards sustainability goals.